Protocol for a systematic review of economic evaluations considering costs and health outcomes of weather and climate-related extreme events in humans - Collins Iwuji; Saeideh Babashahi; Kingsley Orievulu; Ekeminiabasi Eyita-Okon; Dominic Kniveton (BMJ Open)
Background Extreme weather and climate-related events are increasing in frequency and intensity, which pose substantial human casualties and economic losses. The healthcare and health-determining sectors require information about how extreme weather events affect the population’s health, healthcare and other sectors’ capacities to prepare for and manage these events and their aftermath. We aim to conduct a systematic review to identify the recent evidence on the costs and health outcomes of extreme weather events in humans.Methods and analysis The Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines were followed for reporting this protocol. A comprehensive search will be conducted using several search engines, for example, PubMed, Scopus and Institute for Scientific Information Web of Science. Peer-reviewed and grey literature published in English that evaluated the health outcomes and costs of extreme climate events will be retrieved without restriction on the publication year or geographical location. Two reviewers will independently assess each study for inclusion. Study quality will be evaluated with the recommended quality assessment tools. Data will be reported using descriptive statistics, graphical plots and a narrative synthesis.Ethics and dissemination An ethical assessment was not required. The data generated from the systematic review will be disseminated through peer-reviewed journal articles and international conferences and will inform our original research study.PROSPERO registration number This systematic review has been registered at the International Prospective Register of Systematic Reviews (registration ID: CRD42024582635).